2022
DOI: 10.3390/ani12182309
|View full text |Cite
|
Sign up to set email alerts
|

Nociception-Induced Changes in Electroencephalographic Activity and FOS Protein Expression in Piglets Undergoing Castration under Isoflurane Anaesthesia

Abstract: The objective of this study was to investigate the electroencephalographic reaction pattern and FOS protein expression in male piglets undergoing surgical castration under light isoflurane anaesthesia with or without local anaesthesia. The experiment was conducted under isoflurane anaesthesia to exclude the effect of the affective components of pain on the measurements. Changes in the oscillatory activity of the cerebral cortex over a 90 s period after noxious stimulation or simulated interventions were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Nyborg et al [46] showed that injection of a local anesthetic before castration reduced the number of Fos-positive neurons in the dorsal horn. Reiser et al found a significant reduction in the Fos staining score in piglets castrated after an injection of lidocaine, mepivacaine and procaine [47]. Only Mepi1 achieved a significant reduction in Fos protein expression compared to the NaCl castrated piglets in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…Nyborg et al [46] showed that injection of a local anesthetic before castration reduced the number of Fos-positive neurons in the dorsal horn. Reiser et al found a significant reduction in the Fos staining score in piglets castrated after an injection of lidocaine, mepivacaine and procaine [47]. Only Mepi1 achieved a significant reduction in Fos protein expression compared to the NaCl castrated piglets in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…To account for multiple comparisons, instead of a common approach of an alpha level adjustment, we applied a cluster-based approach, as it has been used in the literature both for 2-dimensional (Akeju et al 2014;Kreuzer et al 2020) and 3-dimensional (Lutz et al 2022;Reiser et al 2022) EEG data. We only reported results as being significant if they occurred in clusters of at least 4 × 4 adjacent significant pixels; this translates to a frequency range of 1.5 Hz and a time range of 15 ms.…”
Section: Statisticsmentioning
confidence: 99%
“…To account for multiple comparisons, instead of a common approach of an alpha level adjustment, we have applied a cluster-based approach as it has been used in the literature both for 2-dimensional [45,46] and 3-dimensional [47,48] EEG data. We have only reported results as being significant if they appeared in clusters of at least 3 × 3 pixels in size [36].…”
Section: Statisticsmentioning
confidence: 99%